The Effect of a 12-Week Plyometric and Tabata Training Program with Three Weekly Sessions on Cardiovascular Efficiency in Elite Soccer Players - Nidhin Muthrathiparambil Narayanan; Kayambu Sundar; Nirmal Michael Salvi; Yashpal; Debajit Karmakar; Sohom Saha; Bekir Erhan Orhan; Farjana Akter Boby; Yuni Astuti (Physical Education Theory and Methodology)
Objectives. This study aimed to examine the effects of a 12-week plyometric training program and a Tabata regimen on cardiovascular efficiency in elite soccer players.